Determination of Standard Time and Man Hours for Welding Process in Barge Repairs - Mochammad Falah Adjidinata; Intan Baroroh; Tri Agung Kristiyono; Ali Azhar; Akhmad Basuki Widodo (International Journal of Marine Engineering Innovation and Research, 2025)
Shipyards are facilities that play an important role in building and repairing ships. One common type of repair is replating, which means replacing damaged hull plates with new ones. This process relies heavily on welding, which needs skilled workers and a lot of electrodes. A frequent issue in the field is the challenge of estimating how many electrodes are needed, which often results in wasted materials, increased costs, and delays in completing the work. This study seeks to calculate the electrode needs, the time required for the work, and the man-hours needed for ship replating. The research involved a review of existing literature and a field study. The welding process used the SMAW method with E6013 electrodes, 160A current, and 2G and 3G welding positions. Each welding position involves three stages: root, filler, and capping. The average welding speed data for every 1000 mm is used to calculate the actual welding length in the replating process. The results showed that the average welding time for the 2G position was 39,277.89 minutes, while for the 3G position it was 17,657.54 minutes. The total electrode requirement was 1,619.69 kg, which is equal to 324 boxes, with an estimated cost of Rp. 40,240,800.00. Additionally, the number of workers needed is 27, with a total of 948.924 man-hours over a period of 5 days. In conclusion, organized calculations of electrode needs, time, and man-hours can help improve the efficiency of replating work, reduce waste, and aid in project management planning in shipyards.